EDUCAÇÃO DE JOVENS E ADULTOS: SUJEITOS EGRESSOS. - Dayana de Oliveira Arruda (2022)
The research identified and problematized on the effects of the Education for Youths and Adults with graduates from the High School Education as constituent forms of the Self - subjects graduated from that modality of high school submitted to current ruling, whose certification happened in different times, spaces e specific configurations from that strategy adopted for schooling, having as local the Elvira Mathias de Oliveira High School, linked to the State System of Education of South Mato Grosso, located in the county of Campo Grande. The instruments used as boxes for epistemological tools, as theories and conductions of scientific practices were characterized for advances, step-backs and modifications of systematization, resulting from the horizons of limits and possibilities, given by the Foucaultian referential, that led us in a concrete way sometimes to the meanings and uses of the cartography to fund the research movements, as possibility to join clues and guides in the dialogue within historical and social elements. This dynamics is used as support for critical analysis, sustained by the research subjects, as possible, instrument of resistance and overcoming, the denominated ethical domain, whose analytical possibilities lead to the subjectivation and objectivation processes produce the comprehension of values and rules that belong to the relation of the subject with themselves or about themselves, by the determinants of the social practices, operated by the current culture of segregation, exclusion and tasks, imposing truths and conditions to operate the citizenship experience, rights and schooling. Bunch of relations whose implications correspond to the modes in which the subject, considered constituent, performs subjectivation processes, effect of diverse codification and decoding, in the discrete relation between objectivity and subjectivity, funding its existence by the boundaries of the possible. The systematization of this research in all its circumstances and approaches in reference to the foucaultian theory, assimilated as guideline of the processes in that way, by the cartography as perspective, revealed to us an uncovered reality. We consider a primacy of the itineraries and empirical and analytical evidence by the proper performance, style, and research knowledge linings on which we investigate. As some approximations, we emphasize that the framework of our findings constituted a range of narratives from the research interlocutors, graduates of youth and adult education, composed of expectations, projects, fears, dreams and nightmares, in addition to experiences marked by unique trajectories, confrontations, struggles and personal adversities, self-management strategies, also negotiation of constitutive truths through the subjects' environment, clearly constrained by social, economic, cultural demands and a series of historical and social needs, but marked by desires and wishes, investitures of narrow powers and practices of freedom. They are real games triggered, in this case, by pedagogical practices (self-care) to forge and improve multiple investment strategies and different regimes and forms of body production, in the symbiosis of problems and confrontations. Contingencies of life histories appropriated by institutions and all their processes, the possibilities of creating and reinvigorating gaps of existence for themselves are narrowed, asserting themselves in their own truths and choices. (Re)existences and their games of constituent truths, of a reflective and powerful character, either because they highlight other issues that coexist on the frontiers of the great logic of the ever-improving mechanisms of control, or because they explain processes of subjectivation that institute, by themselves, of knowledge not subjected, promoted in the possible gaps of the moments lived by the graduating subjects, revealing overcoming the control mechanisms, significant and decisive for themselves.